Vitaliy Mikolayovich Levenets - NUPES of Ukraine, Staff of (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2010)
The article deals with the 80th birthday of an outstanding sports traumatologist, Honoured Worker of Science and Engineering of Ukraine, winner of the State Prize of Ukraine in the fields of science and engineering, Doctor of Medical Science, Prof. Levenets Vitaliy Mikolayovich.